Science of Societal Safety Living at Times of Risks and Disasters - Abe, Seiji; Ozawa, Mamoru; Kawata, Yoshiaki (Trust, 2019)
This open access book covers comprehensive but fundamental principles and concepts of disaster and accident prevention and mitigation, countermeasures, and recovery from disasters or accidents including treatment and care of the victims. Safety and security problems in our society involve not only engineering but also social, legal, economic, cultural, and psychological issues. The enhancement needed for societal safety includes comprehensive activities of all aspects from precaution to recovery, not only of people but also of governments. In this context, the authors, members of the Faculty of Societal Safety Science, Kansai University, conducted many discussions and concluded that the major strategy is consistent independently of the type and magnitude of disaster or accident, being also the principle of the foundation of our faculty. The topics treated in this book are rather widely distributed but are well organized sequentially to provide a clear understanding of the principles of societal safety. In the first part the fundamental concepts of safety are discussed. The second part deals with risks in the societal and natural environment. Then follows, in the third part, a description of the quantitative estimation of risk and its assessment and management. The fourth part is devoted to disaster prevention, mitigation, and recovery systems. The final, fifth part presents a future perspective of societal safety science. Thorough reading of this introductory volume of societal safety science provides a clear image of the issues. This is largely because the Japanese have suffered often from natural disasters and not only have gained much valuable information about disasters but also have accumulated a store of experience. We are still in the process of reconstruction from the Great East Japan earthquake and the Fukushima nuclear power plant accident. This book is especially valuable therefore in studying the safety and security of people and their societies.